2018
DOI: 10.1097/bpb.0000000000000524
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment of congenital pseudarthrosis of the tibia: a systematic review and meta-analysis

Abstract: To compare the current treatments for congenital pseudarthrosis of tibia, a total of 33 studies were reviewed. Vascularized fibular graft with external fixation or combined fixation had the fastest time till initial union (P<0.05). Bone morphogenetic protein had no advantage in terms of initial union, time till union, and refracture rates. This meta-analysis supports that fixation methods with corticocancellous bone autograft utilizing the combined technique of Ilizarov external fixation and intramedullary rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 32 publications
3
52
1
4
Order By: Relevance
“…Unfortunately, he failed to keep brace wearing and refracture occurred after trauma. These results were similar or even superior to other studies [ 16 ]. Dobbs et al reported that trans-ankle Williams rod showed satisfactory long-term outcomes, with initial consolidation obtained in 18 (85.7%) of 21 patients and 12 (23.2%) cases of refracture.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unfortunately, he failed to keep brace wearing and refracture occurred after trauma. These results were similar or even superior to other studies [ 16 ]. Dobbs et al reported that trans-ankle Williams rod showed satisfactory long-term outcomes, with initial consolidation obtained in 18 (85.7%) of 21 patients and 12 (23.2%) cases of refracture.…”
Section: Discussionsupporting
confidence: 91%
“…The achievement of skeletal maturity with functional utility and anatomic alignment is the primary goal of treating CPT [ 15 , 16 ]. Due to the high rate of refracture, pediatric surgeons were compelled to focus on successful osteosynthesis rather than the sequelae of CPT, such as joint stiffness and arthritic change led by trans-ankle fixation; metaphyseal irritation and growth failure led by metaphyseal intrusion; and even failure of IM fixation due to inadequate space for nail interlocking in pediatric patients [ 2 , 8 , 10 , 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPT patients commonly have a high rate of fracture recurrence. Bone morphogenetic protein (BMP) in treatment has no advantages in improving initial union, and decreasing the duration between union and refracture episodes [25]. Therefore, genetic and molecular factors rather than an environmental factor are more likely contributing to CPT pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of skeletal maturity with functional utility and anatomic alignment of the bone is the primary goal of treating CPT (3,4). Among various surgical techniques that have been developed to optimize the outcomes in treating CPT, the Ilizarov technique has been proved to be valuable in promoting high rate of union through compression, dealing with limb length discrepancy via diaphyseal transfer and addressing angular deformities concomitantly.…”
Section: Discussionmentioning
confidence: 99%